Interactions between B-lactoglobulin and casein glycomacropeptide on foaming - Martinez, María Julia (2012)
The aim of this work was to study the effect of interactions between casein glycomacropeptide (CMP) and B-lactoglobulin (B-lg) at pH 6.5 and 3.5 on the foaming properties of the mixed systems with different CMP:B-lg ratios. The foaming properties were determined by the bubbling method with a Foamscan instrument. A highest overall foam capacity (OFC), foaming capacity (FC) and mainly stability of mixed foams at pH 3.5, as compared to the mixed foams at pH 6.5 or the foams of CMP and B-lg was observed. At pH 6.5, the stability of mixed foams decreased with increasing the CMP content, while OFC and FC values were similar to B-lg foam. The performance of the mixed systems was discussed in relation with the interactions between CMP and B-lg in the aqueous phase (as observed by dynamic light scattering and differential scanning calorimetry in previous works).